Anomalous Ekman Transport Near Kerguelen Island - Christopher Roach; Helen Phillips; Nathaniel Bindoff; Stephen Rintoul (2012)
In this study we use data from 8 velocity profiling floats to examine the wind driven response of the surface layer of the Southern Ocean north of the Kerguelen Plateau during 2008. Assuming a constant geostrophic velocity within the upper 200m of the ocean we have identified Ekman-like spirals in 249 profiles and in the mean profile. Considering constant geostrophic shear this figure increased to 455 Ekman spirals. Mean Ekman transport was found to be skewed towards the wind, lying at 45° rather than 90° to the left of the wind as expected from steady-state Ekman theory for the Southern Hemisphere. This downwind transport anomaly was found to display little sensitivity to the presence of geostrophic shear or transient wind forcing. We suggest that the anomaly results from the „compression‟ observed in the mean spiral, possibly associated with ocean density stratification.